Assessment of Knowledge, Attitude, and Practices of Food Handlers on Food Safety in Selected Tertiary Hospitals in Metro Manila, Philippines - Abby Rose C. Flores; Jose Ma. C. Angbengco (International Journal of Nutrition Sciences, 2024)
Background: Food safety plays a significant role in the management and recovery of hospitalized patients. This study has assessed knowledge, attitude, and practices of food handlers on food safety in selected tertiary hospitals in Metro Manila, Philippines.Methods: In a cross-sectional analytical design, the knowledge, attitude, and practice levels of 50 food handlers on food safety in four tertiary Metro Manila hospitals were assessed, and the relationship of knowledge, attitude, and practices with sociodemographic characteristics was investigated using a self-administered questionnaire.Results: Food handlers were shown to have fair knowledge (69.73±11.3%), positive attitude (87.8±7.6%), and good practices (84.3±7.8%) on food safety. They had good knowledge on personal hygiene (99%) and cross-contamination (89%), but had poor knowledge on foodborne diseases (42%) and storage temperatures (31%). The majority of the food handlers reported good food safety practices, food safety control, and food storage. No significant association was demonstrated between sociodemographic characteristics and knowledge, attitude, and practices of food handlers regarding food safety. A correlation was observed between attitude (p=0.4431) and practices (p=0.0013) of food handlers on food safety.Conclusion: Food handlers in hospitals in Metro Manila reported positive attitude and good practices on food safety. Improvement in quality of food services through constant and holistic training and evaluation of food handlers seems essential. The strict compliance to food safety standards should be undertaken to ensure the safety and quality of food served to people.